The role of polymorphisms of the MSTN, GRIN2B and DOCK8 genes in the performance of pace-racing Icelandic horses - Bas Conn, Laura (2019)
This study investigated the association of single-nucleotide polymorphisms (SNPs) of three different genes with pace racing performance in the Icelandic horse. The SNPs chosen were PR3737, PR8604 and PR9482 of the Myostatin gene; SNPs g.41206762 C>T and g.41218272 T>C of the GRIN2B gene and SNP g.22496787 T>C of the DOCK8 gene. Icelandic horses that compete frequently in any of the three pace race disciplines (P1 over 250m, P2 over 100m and P3 over 150m) were genotyped for all SNPs mentioned above. The horses in the sample (n=131) were divided into “Speed groups” based on consistency of racing times and training schemes. Three groups were created: Fast (n=37), Average (n=75) and Slow (n=19).